2009
DOI: 10.3892/ijo_00000202
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of PIK3CA is associated with lymph node metastasis in esophageal squamous cell carcinoma

Abstract: Abstract. The genomic region containing PIK3CA was found to be amplified in esophageal squamous cell carcinoma (ESCC) tissue. PIK3CA at 3q26, which encodes the p110· catalytic subunit of phosphatidylinositol (PI) 3-kinase, is a unique intracellular signal transducer characterized by its lipid substrate specificity. In order to characterize PIK3CA in ESCC, we investigated hot-spot mutations in exons 1, 9 and 20, the copy number gain, the expression levels of mRNA and protein. Analysis in exon 9 of the PIK3CA ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 40 publications
7
42
2
1
Order By: Relevance
“…In the present study, ERK and AKT were activated in EC cell lines, including TE1, Eca109 and KYSE 140, which implies that these two activation pathways are important in esophageal tumorigenesis and development. Previous studies have also indicated that both MEK/ERK and PI3K/AKT signaling are activated in ESCC (8,48,49). Therefore, blocking these two pathways is a promising strategy for EC treatment and chemoprevention.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In the present study, ERK and AKT were activated in EC cell lines, including TE1, Eca109 and KYSE 140, which implies that these two activation pathways are important in esophageal tumorigenesis and development. Previous studies have also indicated that both MEK/ERK and PI3K/AKT signaling are activated in ESCC (8,48,49). Therefore, blocking these two pathways is a promising strategy for EC treatment and chemoprevention.…”
Section: Discussionmentioning
confidence: 98%
“…Accumulating evidence indicates that numerous molecular changes are associated with EC tumorigenesis, including epidermal growth factor receptor (EGFR) amplification, phosphoinositide 3-kinase, catalytic subunit alpha (PIK3CA) amplification and mutation (8)(9)(10), and phosphatase and tensin homolog (PTEN) mutation or loss (11,12). Alteration of these molecular events contributes to downstream pathway activation (8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results were analyzed using a 2 tiered (0/1 + vs. 2/3+) and 4 tiered (0 vs. 1vs. 2 vs. 3 +) categorical approach [19].…”
Section: Molecular Correlative Studiesmentioning
confidence: 99%
“…10). In studies of ESCC, PIK3CA mutation has been detected in 2.2% to 11.8% of analyzed cases (11)(12)(13)(14), and its prognostic role has been still unknown. Previous studies in large numbers of cases (more than 200) have shown that PIK3CA mutations are associated with unfavorable prognosis in patients with colorectal (15)(16)(17)(18)(19) or lung cancer (20).…”
Section: Introductionmentioning
confidence: 99%